Climate Smart Agriculture in Golapganj Upazila, Sylhet, Bangladesh: Farmers Perspectives and Challenges (SAARC Journal of Agriculture, 2025)
The farmers of Golapganj upazila in Sylhet district were surveyed on the views of climate-smart agriculture (CSA) practices and their difficulties. A survey was conducted with sixty randomly selected farmers from Gondamara and Turupbag villages in Bagha union, Golapganj upazila, Sylhet district. Validation was conducted using a focus group discussion. The investigation revealed 17 CSA practices in the study area. These practices were high-yielding variety (78.3%), perching (63.3%), adjusting planting time (51.6%), mulching (46.6%), farm yard manure (46.6%), short-duration varieties (46.6%), IPM (43.3%), intercropping (38.3%), crop rotation (38.3%), pheromone trap (35%), local pesticides (35%), improved livestock breed (25%), agroforestry (23.3%), vermicomposting (23.3%), Sorjan (21.6%), light trap (13.3%), rice-cum-fish farming (10%). The adoption of CSA practices was found to be insufficient, with several key techniques underutilized. Respondents valued strip cropping (60.6%), integrated nutrient management (INM) (60%), water harvesting, and pit planting (53.3%) among twelve CSA techniques. The research area did not use seven climate-smart methods for resilient agriculture—strip cultivation, INM, biochar, solar-based irrigation, sandbar cropping, terrace farming, and pit planting. Intervention is possible in both research and extension. They had problems with animal breed (60.6%), technical expertise, and capital (56.6%). A three-tier up-scaling approach (information transfer, entrepreneur development, and policy inclusion) was proposed to enhance CSA adoption in the study area.SAARC J. Agric., 23(1): 1-15 (2025)